Nutritional Characterization of Hay Produced in Campania Region: Analysis by the near Infrared Spectroscopy (NIRS) Technology - Fabio Zicarelli; Fiorella Sarubbi; Piera Iommelli; Micaela Grossi; Daria Lotito; Pietro Lombardi; Raffaella Tudisco; Federico Infascelli; Nadia Musco (Animals, 2022)
Since the dietary characteristics of hays can be very variable, it is of great importance for nutritionists to know their chemical composition in order to formulate adequate rations for the animals. Laboratory analyses are time-consuming and expensive while the Near Infrared Spectroscopy offers several advantages, including obtaining information on feeds nutritional characteristics very quickly and in situ at the farm, thanks to portable NIRS. In this trial, over 400 hay samples collected in the Campania region (Italy) were analyzed with portable NIRS device. The final aim was to analyze the differences in hay quality in different production areas, highlighting the possible factors involved and suggesting possible corrective measures. All the analyzed hays (polyphite, Gramineae and alfalfa) were significantly (p < 0.05) influenced by the area of cultivation/preservation. In particular, the polyphite and Gramineae hays produced in most of the areas of Campania region showed poor nutritional value due to the low protein content and high structural carbohydrate that significantly reduced its digestibility. The use of high-quality forages in the ration represents a pivotal factor to allow the production of high-quality products of animal origin. The use of NIRS seems to be a valuable strategy to select potential treatments that can increase feed digestibility and to avoid long chemical analysis.